Rates and split top-dress applications of N fertilizer in the production of sweet potato in tropical soil - Corrêa, Carla Verônica [UNESP]; Gouveia, Aline Mendes de Sousa [UNESP]; Lanna, Natália de Brito Lima [UNESP]; Martins, Bruno Novaes Menezes [UNESP]; Tavares, Ana Emília Barbosa [UNESP]; Mendonça, Veridiana Zocoler [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Evangelista, Regina Marta [UNESP] (Southern Cross Publishing, 2017)
There are some studies about plant nutrition and split topdress application of fertilizer to influence nutrients and production of sweet potatoes. This study aimed to evaluate the influence of nitrogen doses in the presence or absence of split topdress application on production of sweet potato. A field experiment was conducted at São Manuel Experimental Farm. The experimental design was a randomized complete block with seven treatments (2×3+1 factorial design) and five repetitions. Treatments consisted of three doses of N topdressing (30, 60 and 90 kg Nha-1), two application time (30 and 50 days after shoots sprouting) and a control (without N topdressing). The analysis evaluated roots fresh and dry matter, number of roots, roots length and diameter, roots productivity and the capacity of roots to extract macronutrients. A higher production was observed with multiple application of N fertilizer with 1146.3 g of root per plant. On the other hand, the single application produced an average of 926.7g per plant. A quadratic adjust was obtained with an average of 1209.2 g at 69.2 kg N ha-1 from the single application. However, the yield per hectare did not show any statistical significance in the presence (47.8 t ha-1) or absence (40.1 t ha-1) of split application. The average yield in single application was 52.5 t ha-1 at 75.0 kg N ha-1. On the other hand, the split application produced 54.7 t ha-1 at the highest estimated dose of 85.0 kg N ha-1. The N topdressing reached a statistical significant difference in most of the analysed features. Moreover, the best results obtained from N doses ranging from 60 to 70 kg ha-1.
Keywords: Ipomoea batatas L .; Macronutrients; Nitrogen; Nutrition; Production